(untitled) (Global Journal of Science Frontier Research, 2023)
To study membranes’ acoustic behavior there are several equations concerning their vibration and resonance which help us to understand better their physical properties. In the present paper we want to show the results of the Bessel sinusoid expressions when we change the values of their variables. Because the procedures to solve the Bessel equation are usually not shown in their entirety in books or the Internet this paper explains in detail each step to go from its differential expression to the sinusoid one.